Strategi Pendidik Anak Usia Dini Era Covid-19 Dalam Menumbuhkan Kemampuan Critical Thinking - Mutmainnah (Universitas Lancang Kuning, 2020)
This study aims to look at educators' strategies, ideally in distance learning (online), because when the Covid-19 pandemic appears everything has changed, educators make new strategies in fostering critical thinking in early childhood during a pandemic that hits the whole world, or which is called Covid-19. This research was conducted with a qualitative approach in the form of a case study method to gain knowledge about educators' strategies in developing critical thinking skills in early childhood. Subject selection. Data collection was carried out by using an interactive model with data analysis, namely data reduction, data presentation, drawing conclusions and verification. The results showed that first, during the Covid-19 pandemic children studied at home using distance learning (online); second, there is a strategy from early childhood educators in developing critical thinking skills as long as children learn via long distance (online), that is, children are invited to continue playing while learning even at home, providing an understanding that children are required to wear masks when outside the home, children must use hands sanitizer or washing hands while playing and after playing, explaining to children why they cannot play activities outside home.